2020
DOI: 10.1111/jphp.13188
|View full text |Cite
|
Sign up to set email alerts
|

CircZNF609/miR-134-5p/BTG-2 axis regulates proliferation and migration of glioma cell

Abstract: Objectives MicroRNAs are abundant in eukaryotic cells and play key roles in cancers. Circular RNAs (CircRNAs) served as the competing endogenous RNAs (ceRNAs) in mediating multiple cell processes. This study aims to define the role of CircRNA CircZNF609/miR‐134‐5p in glioma as well as the underlying regulating mechanism. Methods Relative expression of miR‐134‐5p, CircZNF609 and BTG‐2 mRNA was determined by quantitative real‐time PCR. Cell proliferation was analysed by CCK‐8 assay. Cell migration was assessed b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(16 citation statements)
references
References 29 publications
0
16
0
Order By: Relevance
“…10 For example, circZNF609 sequestered miR-134-5p to upregulating BTG-2 to elevate proliferation of glioma cells. 22 CircZNF609 enhanced gastric cancer migration and invasion through modulating CDK6 via sponging miR-483-3p. 23 In this study, we predicted miRNA targets of circZNF609 by CircBank informatic tool.…”
Section: Dovepressmentioning
confidence: 96%
“…10 For example, circZNF609 sequestered miR-134-5p to upregulating BTG-2 to elevate proliferation of glioma cells. 22 CircZNF609 enhanced gastric cancer migration and invasion through modulating CDK6 via sponging miR-483-3p. 23 In this study, we predicted miRNA targets of circZNF609 by CircBank informatic tool.…”
Section: Dovepressmentioning
confidence: 96%
“…CircRNAs are reported to closely associate with the progression of a large number of cancers [5]. Aberrant regulation of circRNAs has been noted in gliomas [6], renal cell carcinomas [7] and other human malignancies [8]. With the development of high-throughput sequencing and bioinformatics analysis, increasing numbers of novel circRNAs have been identified to be potential cancer prognostic biomarkers [9].…”
Section: Introductionmentioning
confidence: 99%
“…MiR-452-5p exerted its function by negatively regulating KAT6B . Mounting data have indicated that circRNAs regulated the miRNA-mRNA axis to affect tumor occurrence and progression in multiple cancers [ 29 , 30 ], certainly including GC [ 31 , 32 ]. In our study, circKIAA0907 had a similar positive regulation on KAT6B expression as a miR-452-5p sponge in GC cells, and KAT6B downregulation could restore the effects of circKIAA0907 on GC cells.…”
Section: Discussionmentioning
confidence: 99%